Advances in the production of biosurfactants as green ingredients in home and personal care products - Nasser, Makary; Sharma, Malvika; Kaur, Guneet (Frontiers in Chemistry, 2024)
Home and personal care industry is currently witnessing a growing demand for sustainable and eco-friendly alternatives to synthetic surfactants. This increase is fueled by concerns over the delayed degradation and environmental impact of the latter. To this, biosurfactants possess important properties such as biodegradability, low toxicity, and renewable sourcing. These qualities position them as compelling replacements of traditional synthetic surfactants. Their diverse attributes including emulsification, antimicrobial efficacy, surface tension reduction, and foaming capability, make them well-suited choices for home and personal care products. Biosurfactants can be produced through several inexpensive and renewable sources which contributes to their commercialization potential. This article discusses various microbial derived biosurfactants including rhamnolipids, sophorolipids, mannosyl-erythritol lipids, trehalolipids and lipopeptides, unraveling and comparing their distinctive roles and advantages in the home and personal care industry. It also focuses on the recent patent innovations in the production of biosurfactants which have aimed at improving their economic viability and performance attributes. Finally, the article sheds light on the challenges and future trajectories for better integration of these sustainable biosurfactants into mainstream consumer products.